Vietnam adopts CCAFS' research on its major climate-smart agriculture-related policies and programs - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Through CCAFS outputs and capacity building activities, the key officials and staff of at least eight offices under the Ministry of Agriculture and Rural Development (MARD) enhanced their knowledge, skills, and attitude towards climate-smart agriculture (CSA). This has enabled the mainstreaming of CCAFSoutputs and inputs in the national policies and key programs.